DAMPAK PEMBERIAN ROTI AFKIR TERHADAP EFISIENSI REPRODUKSI SAPI PERAH Friesian Holstein DI WILAYAH KERJA KPSP SETIA KAWAN NONGKOJAJAR, PASURUAN - Nurdianto S., Ricko; Hidanah, Sri; Madyawati, Sri Pantja; Samik, Abdul; wurlina, wurlina; Suprayogi, Tri Wahyu (Ovozoa: Journal of Animal Reproduction, 2019)
The purpose of this research is to know the impact of bread waste to efficiency reproduction of Friesian Holstein cow in regional working KPSP Setia Kawan Nongkojajar, Pasuruan by value Service per Conception (S/C), Conception Rate (CR), Days Open (DO). Method in this research is the dependent variable observed is the reproductive efficiency, the dependent variable as a supporter is the cow has given birth, the healthy dairy cow, the feed volume given. The data obtained is processed by using descriptive analysis to get the reproduction efficiency figure. The result of the research indicate that the value of Service per Conception (S/C) = 1.5 ± 0.69 times, Days Open (DO) = 95.6 ± 11.32 days and Conception Rate (CR) = 65% and Fertility Status (FS) = 72,4%. Results of this study can be concluded that bread waste provided by the breeder as an additional feed for dairy cow has no significant effect.